2017
DOI: 10.1002/fuce.201600182
|View full text |Cite
|
Sign up to set email alerts
|

Impedance and Raman Spectroscopy Study of Effect of H2S on Ni‐YSZ SOFC Anodes

Abstract: The electrical behavior of a Ni-YSZ anode of a solid oxid fuel cell (SOFC) cell under H 2 S has been monitored by impedance spectroscopy combined with in situ Raman spectroscopy and post mortem scanning electron microscopy (SEM) at 500°C in open circuit potential (OCP) and at 500 mV polarization. In OCP condition, the electrode impedance spectra evolved slowly corresponding quite well to the evolution of Raman signals' intensities. Meanwhile, at 500 mV polarization, the impedance spectra transformed much faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…When Cu-CeO 2 -YSZ anodes were used in conjunction with H 2 contaminated fuel, He et al [58] demonstrated high sulfur tolerance and found that there was no effect on the anode performance at 800 ℃ under 450 ppm sulfur. It is believed that the adsorption of sulfur compounds at the TPB results in a loss of active sites at the TPB and a change of surface characteristics in the case of nickel anode poisoning [8][9][10][11]43]. A further possibility for sulfide formation is that it will affect ceria's oxide transport mechanism and redox chemistry, changing its MIEC properties and potentially diminishing the effective active zone [61].…”
Section: Discussion On H 2 S Poisoning Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…When Cu-CeO 2 -YSZ anodes were used in conjunction with H 2 contaminated fuel, He et al [58] demonstrated high sulfur tolerance and found that there was no effect on the anode performance at 800 ℃ under 450 ppm sulfur. It is believed that the adsorption of sulfur compounds at the TPB results in a loss of active sites at the TPB and a change of surface characteristics in the case of nickel anode poisoning [8][9][10][11]43]. A further possibility for sulfide formation is that it will affect ceria's oxide transport mechanism and redox chemistry, changing its MIEC properties and potentially diminishing the effective active zone [61].…”
Section: Discussion On H 2 S Poisoning Mechanismmentioning
confidence: 99%
“…A rapid initial performance loss is followed by either (i) no further loss, (ii) a slow performance loss followed by steady-state behavior, or (iii) a continuous performance loss without stabilization. It is commonly believed that the sulfur adsorbs at the nickel surface sites or the TPB lead to an initial rapid and reversible performance loss [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%